Establishing a sustainable childhood obesity monitoring system in regional Victoria. (19th December 2016) - Crooks, Nicholas; Strugnell, Claudia; Bell, Colin; Allender, Steve
Abstract : Issue addressed: Childhood obesity poses a significant immediate and long‐term burden to individuals, societies and health systems. Infrequent and inadequate monitoring has led to uncertainty about trends in childhood obesity prevalence in many countries. High‐quality data, collected at regular intervals, over extended timeframes, with high response rates and timely feedback are essential to support prevention efforts. Our aim was to establish a sustainable childhood obesity monitoring system in regional Australia to collect accurate anthropometric and behavioural data, provide timely feedback to communities and build community engagement and capacity. Methods: All schools from six government regions of South‐West Victoria were invited to participate. Passive (opt‐out) consent was used to collect measured anthropometric and self‐reported behavioural data from children in years 2, 4, and 6, aged 7–12 years. Results: We achieved a 70% school participation rate ( n  = 46) and a 93% student response rate ( n  = 2198) among government and independent schools. Results were reported within 10 weeks post data collection. Harnessing high levels of community engagement throughout the planning, data collection and reporting phases increased community capacity and data utility. Conclusions: The monitoring system achieved high response rates, community engagement and community capacity building, and delivered results back to the community in a timely manner. So what?: This system has the potential to provide sustainable monitoring of childhood obesity that is not dependent on external funding. The results of this monitoring will likely inform health promotion efforts in communities across the region. Abstract : Infrequent monitoring has led to uncertainty about trends in childhood obesity prevalence. Our aim was to establish a sustainable childhood obesity monitoring system in regional Australia using a passive (opt‐out) consent process and employing a census‐style sampling technique. This system has the potential to provide sustainable monitoring of childhood obesity, which is vital to understanding the problem of childhood obesity in this region.